Robbing Yadullah's water to irrigate Saeid's garden: hydrology and water rights in a village of Central Iran - Molle, Francois; Mamanpoush, A.R.; Miranzadeh, M. (International Water Management Institute, 2004)
This report provides a case study from the province of Esfahan, in central Iran, describing the struggle of a village to secure the water resources without which local agriculture, and altogether life in the village, would be impossible. It illustrates the endless ingenuity of farmers in their quest for water, how land and water rights have developed, how various legal repertoires may conflict with one another, and how the intervention of the state transformed the wider hydrological cycle of the valley and affected the delicate equilibrium between population and resources that had prevailed until then. The report estimates the costs of accessing one cubic meter from each of these different sources and shows how political interventions or drought mitigation policies elicit solutions that are extremely costly.